2020
DOI: 10.1371/journal.pone.0240556
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence and unmet need for contraception among married and cohabiting women in sub-Saharan Africa: Evidence from demographic and health surveys

Abstract: Introduction Contraception plays a significant role in fertility regulation and determines the reproductive health rights of women. Studies in other parts of the world have found that sexual violence has negative effects on unmet need for contraception. There has not been any study on the association between these two phenomena in sub-Saharan Africa using current nationally-representative survey data. We investigated the association between sexual violence and unmet need for contraception among ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…These obstacles include inadequate knowledge on family planning methods and where they can be accessed, low quality and limited availability of family planning services, and high cost of family planning methods, services, travel, and time. Other obstacles centre around fear of side effects, disapproval from partners and family members, and concerns about moral and social acceptability [ 2 , 5 , 6 ]. These obstacles are more prevalent in adolescent girls and young women (AGYW), and contribute significantly to the high unmet need for contraception among this cohort of women [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These obstacles include inadequate knowledge on family planning methods and where they can be accessed, low quality and limited availability of family planning services, and high cost of family planning methods, services, travel, and time. Other obstacles centre around fear of side effects, disapproval from partners and family members, and concerns about moral and social acceptability [ 2 , 5 , 6 ]. These obstacles are more prevalent in adolescent girls and young women (AGYW), and contribute significantly to the high unmet need for contraception among this cohort of women [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other obstacles centre around fear of side effects, disapproval from partners and family members, and concerns about moral and social acceptability [ 2 , 5 , 6 ]. These obstacles are more prevalent in adolescent girls and young women (AGYW), and contribute significantly to the high unmet need for contraception among this cohort of women [ 2 , 6 ]. This may explain the approximately 80 million mistimed and unplanned pregnancies, which occur in low-and middle-income countries, and constitute 40% of all pregnancies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally unmet need for Family planning has always been a major public health concern over decades leading to mistimed and unwanted pregnancies and induced abortions. This is negatively associated with the social, economic and health issues of women and their families (Ahinkorah et al, 2020). Evidence suggests that the COVID 19 pandemic has disrupted access to all family planning information and services.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that infectious diseases, including acute respiratory infections, measles, malaria and diarrhoea are leading direct causes of U5D, while the indirect causes are most especially the socio-economic, environmental and behavioural factors (6). Difficulties associated with accessing fundamental lifesaving care such as the skill of birth attendant, postnatal care, adequate dietary intake, and vaccinations against common childhood diseases also predispose children to the risk of dying before the age of five years.…”
Section: Introductionmentioning
confidence: 99%